Market and climatic risks and farmers' investment in productive assets under the Second Fadama Development Project in Nigeria - Takeshima, Hiroyuki; Yamauchi, Futoshi (International Food Policy Research Institute, 2010)
The majority of African farmers lack the means to mitigate the impact of risks such as those associated with rainfall and commodity prices. Because most farmers in Sub-Saharan Africa are risk-averse, they may be willing to invest in productive assets that can mitigate the impacts of such risks if their capital constraints are relaxed through external financial assistance. We test this hypothesis using panel data on Nigerian farmers' investment behaviors collected during the Second National Fadama Development Program (Fadama II), which provided financial assistance to farmers in obtaining various productive assets, as well as historical data on rainfall and white gari price in various locations in Nigeria. The results support the hypothesis. Under the Fadama II, farmers facing higher rainfall risk (coefficient of variation in annual rainfall) were more likely to invest in irrigation pumps that can mitigate the impact of rainfall risk, and those facing higher risks on white gari price were more likely to invest in milling machines that enable them to process cassava into flour instead of gari.